EQUIVALENCE AND TRANSLATION QUALITY ASSESSMENT TOWARDS NEWS TRANSLATION: VICE INDONESIA YOUTUBE CHANNEL - Era Basriana; Esti Junining; Sri Endah Tabiati (Journey: Journal of English Language and Pedagogy, 2022)
Translation, along with technological advancement, has been a critical step in enabling the journalistic message to transcend territorial borders. This study aims to determine the type of equivalence contained in the news translation of VICE Indonesia YouTube channel and its impact on the translation quality. The data were taken from the subtitle transcript of VICE Indonesia. This research was conducted by using qualitative descriptive method. Several theories were elaborated within this research namely, Nida & Taber theory of equivalence (cited in Panou, 2013, p.2) and the equivalence theory of Baker (2018), and the adopted model of translation quality assessment from Nababan et al. (2012). The results of this study showed that there were six types of equivalence found within the subtitles: formal equivalence, dynamic equivalence, equivalence at word level, equivalence above word level, grammatical equivalence, and pragmatic equivalence. Grammatical equivalence is the type that dominates the overall data. Furthermore, the findings shows that 66.67% of samples were categorized as less communicative, 58.33% of samples were evaluated as unacceptable translations, and 38.89% of the sample scored as high readability level.